Toxicity of depleted uranium complexes is independent of p53 activity - Heintze, Ellie (2010)
The p53 tumor suppressor protein is one of the key checkpoints in cellular response to a variety of stress mechanisms, including exposure to various toxic metal complexes. Previous studies have demonstrated that arsenic and chromium complexes are able to activate p53, but there is a dearth of data investigating whether uranium complexes exhibit similar effects. The use of depleted uranium (DU) has increased in recent years, raising concern about DU’s potential carcinogenic effects. Previous studies have shown that uranyl acetate and uranyl nitrate are capable of inducing DNA strand breaks and potentially of inducing oxidative stress through free radical generation, two potential mechanisms for activation of p53. Based on these studies, we hypothesized that either uranyl acetate or uranyl nitrate could act as an activator of p53. We tested this hypothesis using a combination of cytotoxicity assays, p53 activity assays, western blotting and flow cytometry. All of our results demonstrate that there is not a p53-mediated response to either uranyl acetate or uranyl nitrate, demonstrating that any cellular response to uranium exposure likely occurs in a p53-independent fashion under the conditions studied.